Pairing community health workers with HPV self‐sampling for cervical cancer prevention in rural Haiti1. Issue 3 (11th November 2014) - Mandigo, Morgan; Frett, Brigitte; Laurent, Jean Robert; Bishop, Ian; Raymondville, Maxi; Marsh, Sarah; Kobetz, Erin
Abstract: Objective: To assess a program in which community health workers (CHWs) provided women with self‐sampling devices to detect high‐risk human papillomavirus (HPV). Methods: In a cross‐sectional study, 13 CHWs visited homes in a rural area in Haiti's Central Plateau to recruit premenopausal women aged 30–50 years between July 2009 and April 2010. Eligible women had not undergone a cervical smear in the previous 3 years. Participants learned about cervical cancer and self‐sampling for HPV testing before using a self‐sampler in private. They then completed a questionnaire. CHWs later returned to provide results and advice about follow‐up care. Results: CHWs enrolled 493 women. Among the 485 women for whom questionnaires were received, 468 (96.5%) were comfortable using the self‐sampler and 484 (99.8%) stated they would recommend it to others. Among 426 analyzed samples, 54 (12.7%) were positive for high‐risk HPV, of whom 46 (85.2%) received follow‐up care and 17 (31.5%) had precursor lesions and were treated. Conclusion: Using a CHW‐led intervention, women at high risk for developing cervical cancer were identified and navigated to preventive care. Therefore, pairing CHWs with HPV self‐sampling is a promising strategy to combat cervical cancer in rural Haiti and similar settings.